2015
DOI: 10.1002/bate.201500078
|View full text |Cite
|
Sign up to set email alerts
|

Scheibenschub von Brettsperrholz: Verifizierung einer Prüfkonfiguration und Parameterstudie

Abstract: Shear properties of cross laminated timber diaphragms: verification of a test configuration and parameter studyIn diaphragms of cross laminated timber (CLT) exposed to shear the internal structure of orthogonally layered side bonded layers leads to three possible failure mechanisms: (i) grossshear, (ii) net-shear and (iii) torsion. While the resistance against torsion has been investigated comprehensively, the determination of gross-and net-shear strength values remained a challenging task. Present design conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…A single characteristic value of f v,gross,k = 3.50 MPa was suggested in [3], considering shrinkage cracks by reducing the thickness of exterior layers by 50% when determining t gross . For net shear failure (FM II), the determination of net shear strength is not so straightforward, see [23][24][25], and no values for the strength class of the laminations were provided in EN 338 [22]. Based on the most recent comprehensive experimental study [3], a conservative reference net shear strength of f v,net,k,ref = 5.50 MPa is proposed for layer thicknesses t < 40 mm, while for layer thicknesses 20 < t < 40 mm, the net shear strength is provided as follows:…”
Section: Design Verificationmentioning
confidence: 99%
“…A single characteristic value of f v,gross,k = 3.50 MPa was suggested in [3], considering shrinkage cracks by reducing the thickness of exterior layers by 50% when determining t gross . For net shear failure (FM II), the determination of net shear strength is not so straightforward, see [23][24][25], and no values for the strength class of the laminations were provided in EN 338 [22]. Based on the most recent comprehensive experimental study [3], a conservative reference net shear strength of f v,net,k,ref = 5.50 MPa is proposed for layer thicknesses t < 40 mm, while for layer thicknesses 20 < t < 40 mm, the net shear strength is provided as follows:…”
Section: Design Verificationmentioning
confidence: 99%
“…Table 2 concerns small specimens and verification of FM III, while Table 3 involves large specimens and FM II. An extensive experimental testing was conducted by Brandner et al [59] in 2015 on prisms subjected to compression load, as shown in Figure 12. Test results and varied experimental parameters are shown in Table 3.…”
Section: Shear Strengthmentioning
confidence: 99%
“…or FM III[31,55,56]. The tests on large specimens have been oriented toward determination of FM II[57][58][59].Figure 11shows experimental setups from small models, andFigure 12shows specimens from large models. Summary…”
mentioning
confidence: 99%
“…Durch eine Stauchung in Längsrichtung werden im Probekörper Schub‐ ( τ xMyM ) und Querdruckspannungen ( σ yM ) hervorgerufen (Bild mittig), sodass eine Prüfung der Schubtragfähigkeit unter Vorhandensein einer zusätzlichen Querdruckbeanspruchung erfolgt. Da die Interaktionsbeziehung zwischen Schubfestigkeit und Querdruckbeanspruchung bekannt ist , kann eine Bereinigung der beobachteten Schubtragfähigkeiten um den (günstigen) Einfluss der Querdruckbeanspruchung erfolgen . Die Eignung des gewählten Prüfverfahrens, das ursprünglich für die Ermittlung von Eigenschaften unter quasistatischer Beanspruchung entwickelt worden ist, konnte für Ermüdungsversuche im Rahmen der Versuche grundsätzlich bestätigt werden .…”
Section: Versuchskonzeptunclassified